MANAGEMENT OF THE UNDERWATER AND COASTAL ARCHAEOLOGICAL HERITAGE IN ISRAEL’S SEAS (II): THE ENDANGERED COASTAL SETTLEMENTS - Galili, Ehud; Arenson, Sarah (Riparia, 2016)
The two articles titled Management of the underwater and coastal archaeological heritage in Israel’s seas – parts A and B aim at presenting the diversity, nature and significance of an important cultural resource at risk, namely the underwater and coastal archaeological sites of Israel. Part I introduces the typology of the sites on the Mediterranean coast and the inland seas (The Sea of Galilee and the Dead Sea). Part II presents the main endangered sites along the Mediterranean coast of Israel, their archaeological and historical significance, the risks they are facing and the measures that have to be taken in order to ensure their long term preservation.